Mechanistic Studies on the Hexadecafluorophthalocyanine–Iron‐Catalyzed Wacker‐Type Oxidation of Olefins to Ketones. Issue 67 (27th October 2021) - Puls, Florian; Seewald, Felix; Grinenko, Vadim; Klauß, Hans‐Henning; Knölker, Hans‐Joachim
Abstract: The hexadecafluorophthalocyanine–iron complex FePcF16 was recently shown to convert olefins into ketones in the presence of stoichiometric amounts of triethylsilane in ethanol at room temperature under an oxygen atmosphere. Herein, we describe an extensive mechanistic investigation for the conversion of 2‐vinylnaphthalene into 2‐acetylnaphthalene as model reaction. A variety of studies including deuterium‐ and 18 O2 ‐labeling experiments, ESI‐MS, and 57 Fe Mössbauer spectroscopy were performed to identify the intermediates involved in the catalytic cycle of the oxidation process. Finally, a detailed and well‐supported reaction mechanism for the FePcF16 ‐catalyzed Wacker‐type oxidation is proposed. Abstract : How does it work ? Herein, we describe our detailed mechanistic studies on the iron‐catalyzed oxidation of olefins to ketones. Isotopic labeling studies (deuterium and 18 O) and Mössbauer spectroscopy led to an advanced mechanism for the catalytic cycle.